2007
DOI: 10.1002/rcm.2832
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography/mass spectrometry analysis of PHY906, a Chinese medicine formulation for cancer therapy

Abstract: PHY906 is a Chinese medicine formulation prepared from four medicinal herbs for adjuvant cancer chemotherapy. In this paper, liquid chromatography/electrospray ionization time-of-flight mass spectrometry (LC/ESI-TOFMS) was used to clarify the chemical composition of PHY906. The aqueous extract of PHY906 was separated on a Waters Atlantis C(18) column, and was eluted with acetonitrile/0.05% (v/v) formic acid. The separated compounds were identified with pure standards, or tentatively characterized by analyzing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 31 publications
(37 reference statements)
4
66
0
2
Order By: Relevance
“…Many papers have been published proling phenolic compounds in G. glabra samples from different origins and using different extraction methodologies, some of them cited in the previous discussion. 34,35,[37][38][39][40][41][42][43][44][45][46] However, from all of them, only Montoro et al (2011) presented quantitative results, although they cannot be compared with ours results since they are expressed differently (mg g À1 of dry plant), thus these authors revealed liquiritin apioside as the main avonoid present in their sample, which is in agreement with the sample studied herein. In our case, the results were expressed in mg g À1 of extract in order to relate the amounts of phenolic compounds found in the extract to the antioxidant activity.…”
Section: Finally It Was Not Possible To Identify Compound 11 With a supporting
confidence: 83%
“…Many papers have been published proling phenolic compounds in G. glabra samples from different origins and using different extraction methodologies, some of them cited in the previous discussion. 34,35,[37][38][39][40][41][42][43][44][45][46] However, from all of them, only Montoro et al (2011) presented quantitative results, although they cannot be compared with ours results since they are expressed differently (mg g À1 of dry plant), thus these authors revealed liquiritin apioside as the main avonoid present in their sample, which is in agreement with the sample studied herein. In our case, the results were expressed in mg g À1 of extract in order to relate the amounts of phenolic compounds found in the extract to the antioxidant activity.…”
Section: Finally It Was Not Possible To Identify Compound 11 With a supporting
confidence: 83%
“…15,16 Previous reports contributed much to supporting the wide use of OTS and the herb. Most of these studies, however, were focused on quantitative analysis of one or a few OTS in licorice.…”
mentioning
confidence: 98%
“…Хроматографический пик по сигналу ионного перехода с m/z = 821 → 193 был зарегистрирован с близким к пику глицирризина временем удержива-ния (8.8 мин) в экстракте из листьев A. precatorius и соответствовал абрусозиду D, молекула которого включает только один остаток глюкуроновой кис-лоты. Таким образом, в проведенном эксперименте показано, что метод ВЭЖХ-МС/МС, с применением двух ионных переходов, позволяет успешно иден-тифицировать и определять глицирризин, а реко-мендация авторов работы [23] -использовать ха-рактеристичный фрагментный ион с m/z = 351 для быстрой идентификации сапонинов корня солодки может быть применена к препаратам и продуктам, одновременно содержащим экстракт корня солод-ки и женьшеня, а также листьев A. precatorius. Од-нако, учитывая многообразие используемых в ТКМ растений, нельзя гарантировать, что другие компо-ненты, содержащие цепочку из двух сахаридных остатков глюкуроновой кислоты, не будут мешать такому определению глицирризина и его аналогов в комплексных препаратах.…”
Section: таблицаunclassified
“…Наиболее часто применяемым методом определения глицирризина на сегодняшний день является ВЭЖХ-МС/МС [20,21]. Для количествен-ной оценки содержания глицирризина и его ана-логов измерения проводят в режиме регистрации выбранных ионных переходов, так было показано, что для всех обнаруженных сапонинов фрагмент-ными ионами были депротонированные молекулы глюкуронозил-(1,2)-глюкуроновой кислоты (m/z = 351), глюкуроновой кислоты (m/z = 193) и ее произ-водного с отщеплением молекулы H 2 O (m/z = 175) [22,23]. В некоторых работах для быстрого скри-нинга пищевых добавок и средств ТКМ применяют ВЭЖХ-МСВР, используя времяпролетные масс-ана-лизаторы [24] и орбитальную ионную ловушку [25].…”
Section: Introductionunclassified